2019
DOI: 10.1136/heartjnl-2019-314879
|View full text |Cite
|
Sign up to set email alerts
|

Calcification and extracellular matrix dysregulation in human postmortem and surgical aortic valves

Abstract: ObjectivesCalcific aortic valve disease (CAVD) is a progressive disease ranging from aortic valve (AoV) sclerosis to AoV stenosis (AS), characterised by severe calcification with impaired leaflet function. Due to the lack of early symptoms, the pathological progression towards valve dysfunction is poorly understood. The early patterns of AoV calcification and altered extracellular matrix (ECM) organisation were analysed in individuals postmortem without clinical AS compared with clinical AS.MethodsHistological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 25 publications
4
31
1
Order By: Relevance
“…[ 26 28 ] In addition, ECM organization is one of the hallmarks of CAVD which have been reported previously. [ 29 , 30 ] CAV is characterized by fibrotic thickening of the valve leaflets, inflammation, neoangiogenesis, calcification, and the presence of other ectopic mesenchymal tissues, especially in the fibrosa layer. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 28 ] In addition, ECM organization is one of the hallmarks of CAVD which have been reported previously. [ 29 , 30 ] CAV is characterized by fibrotic thickening of the valve leaflets, inflammation, neoangiogenesis, calcification, and the presence of other ectopic mesenchymal tissues, especially in the fibrosa layer. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…' An understanding of the cellular and molecular mechanisms of calcific aortic stenosis (AS) might allow targeted medical therapy to prevent disease initiation and progression. Gomez-Stallons and colleagues 3 compared histological patterns of aortic valve leaflet calcification in patients with and Heart November 2019 Vol 105 No 21 Heartbeat Figure 3 (1) Robust in vivo screening combined with radiotracers or near-infrared fluorescent calcium tracer to track the progression of calcific aortic valve disease in high-risk populations (hypertension, diabetes, hyperlipidaemia, bicuspid aortic valve) for early intervention and screening should be performed in parallel with (2) next-generation 'omics' techniques that enable collection and study of the entire genome, miRNAome, transcriptome, proteome and secretome. 3The massive amount of data generated by this multi-omics approach is increasingly being analysed with the aid of artificial intelligence, where machine learning algorithms are employed to identify the most promising drug targets.…”
Section: Figurementioning
confidence: 99%
“…Proteoglycans are negatively charged molecules capable of promoting lipid retention [10] as well as transforming growth factor beta (TGF-β) retention [11], a cytokine known to promote VIC trans-differentiation [12]. Observational studies have revealed that regions with moderate calcification exhibit an expansion of the proteoglycan content towards the fibrosa layer of the valve [13] and that these proteoglycans tend to accumulate in the surroundings of calcified nodules [14]. Importantly, these observations have been confirmed with proteomics, revealing that fibrotic parts of the valve present higher levels of proteoglycans [15], specifically proteoglycan 4 (PRG4).…”
Section: Introductionmentioning
confidence: 99%